Perancangan Pengelolaan Data Presensi Sidik Jari Berbasis Web dalam Dunia Pendidikan (Studi Kasus : Institut Shanti Bhuana) - Paulus Alfianus; Benecta Ina Purwanti; Noviyanti P (Journal of Information Technology, 2022)
Currently, we see that in the teaching and learning process, there are many campuses that still use manual attendance, even though the world is now very sophisticated when viewed in terms of technological developments. The problem that arises is why campuses don't use online attendance, for example using website-based fingerprints or what we are familiar with with fingerprint machines that aim to prevent cheating in attendance, for example cheating in attendance that takes advantage of classmates. By applying fingerprints online it will be very helpful in preventing fraud in attendance. With a fingerprint, it can also help solve problems, for example, there are students who come or go home at the appointed time, it will be seen when students come and go. Not only that, lecturers are also easy to collect data to recap student attendance. And by applying the presence of attendance using this fingerprint can make it easier for lecturers to recap the attendance of each student.